A Modified Radiographic Technique to Confirm the Attachment Seating in Auricular Prostheses: A modified radiographical technique for auricular prostheses - Ghoveizi , Rahab; Tavakolizadeh, Sara; Beyabanaki, Elaheh (Journal of Dental School, 2021)
Objectives Implant-retained maxillofacial prostheses have proven to be more successful than conventional adhesive-retained prostheses. Implants enhance prosthesis stability and retention through retentive attachments. However, a faulty abutment-implant interface in terms of complete seating and passive fit could be responsible for mechanical and/or biological complications. This case report describes a simple imaging method to check this adaptation. Case: In our case, two shoulder type maxillofacial implants with 4 mm length and diameter were placed with 15 mm distance using a surgical guide. After completion of the healing course and making an impression, a metal bar attachment was made and tried on. In addition to using conventional methods to check the complete and correct seating of the suprastructure (bar attachment), a modified posterior-anterior radiograph with a 15-degree downward head tilt was taken. After confirming the seating of the attachment, the auricular prosthesis was made accordingly. Conclusion Use of radiography to ensure the seating of intraoral implant-supported frameworks is common and accurate. However, there is no radiographic imaging method to check the fit of extraoral implant-supported substructures. This case report described a simple and effective radiographic technique for auricular implant supported by a substructure which is especially important in case of presence of thick skin around the implants, which compromises the accuracy of direct exploring.